PLURALISME PENYELENGGARAAN PENDIDIKAN BERBASIS KEAGAMAAN KRISTEN DAN KATOLIK DI KABUPATEN BANGKALAN - Wardhana, Indra Jaya Kusuma; Prastiwi, Merlia Indah; Suseno, Klaudius Febrianto Ari (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
This research aims to take a space that has not received attention in the field of education that intersects with the complexity of community elements towards religious minority groups. Therefore, it is important to tackle the conception of pluralism in the implementation of non-Muslim religious-based education as a representation of the diversity of multicultural values of Madura. This research uses a qualitative methodology with an ethnomethodological approach. This study focuses on the assumption of "subjectivity" through the interpretive actions of community members who produce and organize daily experiences related to inter-religious tolerance values. The focus of this study concern a views of stakeholders, including the organizational structure of educational institutions and local government officials regarding the implementation of non-Muslim religious-based education as a representation of minority groups. Bangkalan Regency was chosen as the research location, referring to the highest proportion of Christian and Catholic population among the four regencies on Madura Island. The results of this study show the attitude of tolerance between religious communities as a representation of pluralism, especially for religious minority groups in the field of education provision that occurs in Bangkalan Regency.